67 cm long bismuth-based erbium doped fiber amplifier with wideband operation - Xiau, San Cheng; Hamida, Belal Ahmed; Ahmed Wathik, Naji; Harith B., Ahmad; Harun, Sulaiman Wadi (Wiley - VCH Verlag GmbH & CO. KGaA, 2011)
In this paper, we demonstrate a wideband Bismuthbased erbium doped fiber amplifier (Bi-EDFA) using two pieces of bismuth-based erbium-doped fiber (Bi-EDF) with a total length of 67 cm as gain media in a double pass parallel configuration. Both Bi-EDFs have an erbium ion concentration of 6300 ppm. Compared to conventional silica-based erbiumdoped fiber amplifier (Si-EDFA) with the same amount of erbium ions, the Bi-EDFA provides a higher attainable gain as well as a greater amplification bandwidth, which ranging from 1525 to 1620 nm. The proposed Bi-EDFA achieved a wideband gain of around 18 dB within the wavelength region from 1530 to 1565 nm. The noise figures are maintained below 10 dB within a wide wavelength region from 1535 nm to 1620 nm. © 2011 by Astro Ltd., published exclusively.